Microstress cycle and contact fatigue of spiral bevel gears by rolling-sliding of asperity contact - Cao, Wei; Ren, Si; Pu, Wei; Xiao, Ke (Friction, 2020)
The rolling contact fatigue (RCF) model is commonly used to predict the contact fatigue life when the sliding is insignificant in contact surfaces. However, many studies reveal that the sliding, compared to the rolling state, can lead to a considerable reduction of the fatigue life and an excessive increase of the pitting area, which result from the microscopic stress cycle growth caused by the sliding of the asperity contact. This suggests that fatigue life in the rolling-sliding condition can be overestimated based only on the RCF model. The rubbing surfaces of spiral bevel gears are subject to typical rolling-sliding motion. This paper aims to study the mechanism of the micro stress cycle along the meshing path and provide a reasonable method for predicting the fatigue life in spiral bevel gears. The microscopic stress cycle equation is derived with the consideration of gear meshing parameters. The combination of the RCF model and asperity stress cycle is developed to calculate the fatigue life in spiral bevel gears. We find that the contact fatigue life decreases significantly compared with that obtained from the RCF model. There is strong evidence that the microscopic stress cycle is remarkably increased by the rolling-sliding motion of the asperity contact, which is consistent with the experimental data in previous literature. In addition, the fatigue life under different assembling misalignments are investigated and the results demonstrate the important role of misalignments on fatigue life.